A feasibility study of a dedicated senior citizens area in the Quezon City Public Library main branch - Precilla, Peter Joseph A. (2011)
This thesis looked at the Quezon City Public Library Main Branch and evaluated its budget, resources, and programs to see if it could sustain a dedicated area catered to the needs of its elderly population. The needs and interests of seniors in Quezon City are also looked at in order to see what improvements should be implemented. The purposes of this study are to improve the quality of services given to this age group and increase the number of senior citizens who visit the QCPL.